The Influence of Management Capability, Marketing Capability and Competitive Advantage on Malaysian Construction Project Performance - Jolly, Baderisham; Isa, Filzah Md; Othman, Siti Norezam; Ahmdon, Muhd Afiq Syazwan (International Review of Management and Marketing, 2016)
Many construction projects in Malaysia experience a reducing performance. There are many factors affecting the performance of construction projects such as poor site management, inadequate planning, ineffective marketing efforts, etc. which usually lead to project delay and cost overrun. Thus, the purpose of this study was to examine the influence of management capability, marketing capability and competence advantage on Malaysian construction project performance. The sample size of this study was 420 selected construction company's project managers. The hypothesis of this study confirmed the management capability, marketing capability and competence advantage have a relationship with the success of project performance. This research brings a better understanding of the success factors for Malaysian construction project performance. Keywords: Management capability, marketing capability, competence advantage, project management JEL Classifications: l25, M10